Komposisi Organik Kapital Industri Media di Era Konvergensi, Studi Kasus Konvergensi Pikiran Rakyat - Muhammad Ashari (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
This article examines the convergence strategy in Pikiran Rakyat media. The convergence strategy is analysed using the Organic Composition of Capital Theory from Karl Marx (1887). The theory describes the interaction between technological improvement (constant-capital) and labour mobilisation (variable-capital) in the production process, which its primary goal is to generate profits for the capitalist. This article highlights technological change, driven by the tendency of capitalism to maximise profit and its consequences for the journalists. The used method for analysis is case study. Data for analysis are collected from documents, interviews, and participant observations. The result indicates that the improvement of Pikiran Rakyat constant-capital, concerning its convergence strategy, is done by integrating the content of all its subsidiaries through newsroom and e-mail, which have the purpose of disseminating news content to various platforms. There is an increase in the number of contents from these efforts. However, it also has a consequence for journalists and editors who are forced to produce news for various platforms.